Assessing the impact of medical studies on students’ motivation, satisfaction, stress and values in Poland: a cross-sectional study - Pola Sarnowska; Julia Terech; Klaudia Bikowska; Mateusz Guziak; Maciej Walkiewicz (BMC Medical Education)
Abstract Background The demanding nature of the medical career path leads to reflection on the motivations, values and expectations of medical students towards their course, their satisfaction with its components and the stress they experience. Research suggests that these parameters may change in the course of the studies, which may be linked to varying forms of the training and students’ personal circumstances. The following study aimed to analyse differences in these areas across various stages of medical education. Methods A total of 334 Polish medical students in 1st, 4th and 6th year were surveyed. The study included questionnaires to assess motivations for choosing medical studies, satisfaction with them, students’ values, competencies developed during the studies and the Brief Resilience Scale. Additional questions addressed students’ life situation and stress levels, preferred medical specialties, and alternative career paths. The Mann-Whitney U test with Benjamini-Hochberg p-value correction was applied to analyse motivation, health and stress levels, and satisfaction. Fisher’s exact test with Benjamini-Hochberg p-value correction was applied to assess life values, competencies, medical specialty preferences and alternative paths. Results Significant differences were found in motivations to study such as interests, high income and social prestige, as well as in health assessment and stress levels, satisfaction with the university, relationships with peers and teachers, various classes, practical skills, workload and time spent on studies. Life values showed shifts in the importance of peace and quiet, education, achievement and fame. Competencies gained and expected to develop differed by the year of study. Resilience levels showed no significant changes across the groups. Few notable results were found regarding the changes in specialty preferences or consideration of alternative career paths. Conclusions As students advance in their medical education, extrinsic motivations such as financial gain and prestige become less prominent, but intrinsic motivations like interest in the subject also decrease. Satisfaction with medical education diminishes over time, particularly in areas related to the university, relationships, or skills. Values such as achievement, fame and education gradually become less important. Interpersonal and analytical skills appear to develop more prominently in the later stages of training. Stress levels typically peak around the fourth year of study.